Can Hypothyroidism Cause Acute Central Serous Chorioretinopathy?. (17th November 2019) - Ulaş, Fatih; Uyar, Enes; Tekçe, Hikmet; Çelebi, Serdal
ABSTRACT: Purpose : To evaluate selected systemic findings, especially thyroid functions, in acute central serous chorioretinopathy (CSC) patients. Materials and Methods : In all, 71 consecutive acute CSC patients who fulfilled the inclusion criteria and 70 age-matched healthy control subjects were included in the study. Systemic findings, including serum levels of thyroid hormones, thyroid stimulating hormone (TSH), mean arterial pressure (MAP), pulse rate, serum lipid levels and optical coherence tomography findings, were compared between the groups. Independent samples t-test was used for statistical analysis. Results : The mean ages of the CSC and control groups were 41.06 ± 6.49 and 40.06 ± 7.08 years old, respectively. Retinal thickness, choroidal thickness, TSH levels, pulse rate and MAP were significantly different between CSC patients and healthy control subjects (range of p values: <0.001–0.042). In the logistic regression analysis, MAP, serum triglyceride concentration and central choroidal thickness were positively associated with CSC (range of p values: <0.001–0.035). Conclusion : Acute CSC patients had significantly higher pulse rates and MAP and significantly thicker choroidal thickness than were found in healthy subjects. TSH levels were also significantly higher in CSC patients than in controls. Hence, hypothyroidism might be associated with CSC.